Implication And Application MBKM’s Curriculum In Education (Madrasah And Universities) - Dian Dian; Chyril Futuhana Ahmad; Fathur Riyadhi Arsal; Siti mahmudah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
The Indonesian government has recently implemented a new education policy called